A POSSIBLE PALEOCLIMATIC IMPLICATION OF A RECENT CHANGE OF CORRELATIONS BETWEEN THE TREE-GROWTH AND THE CURRENT WARMING - Nina Datsenko; Nadezhda Ivashchenko (Geography, Environment, Sustainability)
Recent studies have revealed a reduced sensitivity of tree-growth to temperature at high Northern Hemisphere (NH) latitudes during recent decades. Causes of this reduction are not known, but it seems to be for certain that this reduction has important implications for paleoclimatic reconstructions based on tree-rings because there is a risk that warmer phases of paleoclimates can be essentially underestimated if the problem is not taken into account. We add some more observational evidences of the reduction and argue: it is a signal that temperatures recently have reached above optimum levels for the tree-growth in some areas of NH. If such equally warm, or warmer, phases existed in the past, and if tree-growth responded negatively to temperatures during these phases, it would be necessary to apply separate transfer functions to calibrate tree-ring records in terms of temperature for warmer and colder phases of the past climates.